Impact of electronic healthcare-associated infection surveillance software on infection prevention resources: a systematic review of the literature. Issue 1 (May 2018) - Russo, P.L.; Shaban, R.Z.; Macbeth, D.; Carter, A.; Mitchell, B.G.
Summary: Background: Surveillance of healthcare-associated infections is fundamental for infection prevention. The methods and practices for surveillance have evolved as technology becomes more advanced. The availability of electronic surveillance software (ESS) has increased, and yet adoption of ESS is slow. It is argued that ESS delivers savings through automation, particularly in terms of human resourcing and infection prevention (IP) staff time. Aim: To describe the findings of a systematic review on the impact of ESS on IP resources. Methods: A systematic search was conducted of electronic databases Medline and the Cumulative Index to Nursing and Allied Health Literature published between January 1 st, 2006 and December 31 st, 2016 with analysis using the Newcastle–Ottawa Scale. Findings: In all, 2832 articles were reviewed, of which 16 studies met the inclusion criteria. IP resources were identified as time undertaken on surveillance. A reduction in IP staff time to undertake surveillance was demonstrated in 13 studies. The reduction proportion ranged from 12.5% to 98.4% (mean: 73.9%). The remaining three did not allow for any estimation of the effect in terms of IP staff time. None of the studies demonstrated an increase in IP staff time. Conclusion: The results of this review demonstrate that adopting ESS yields considerable dividends in IP staff time relating to data collection and case ascertainment while maintaining high levels of sensitivity and specificity. This has the potential to enable reinvestment into other components of IP to maximize efficient use of scarce IP resources.